Measuring Education Inequality : Gini Coefficients of Education - Thomas, Vinod; Wang, Yan; Fan, Xibo (World Bank, Washington, DC, 2014)
The authors use a Gini index to measure inequality in educational attainment. They present two methods (direct and indirect) for calculating an education Gini index, and generate a quinquennial data set on education Gini indexes for the over-15-population in 85 countries (1960-90). Preliminary empirical analysis suggests that: 1) Inequality in education in most of the countries declined over the three decades, with a few exceptions. 2) Inequality in education as measured by the education Gini index is negatively associated with average years of schooling, implying that countries with higher educational attainment are more likely to achieve equality in education, than those with lower attainment. 3) A clear pattern of an education Kuznets curve exists if the standard deviation of education is used. 4) Gender gaps are clearly related to education inequality, and over time, the association between gender gaps, and inequality becomes stronger. 5) Increases in per capita GDP (adjusted for purchasing power parity) seem to be negatively associated with education inequality, and positively related to labor force's average years of schooling, after controlling for initial income levels.